2016
DOI: 10.1021/acs.est.6b01978
|View full text |Cite
|
Sign up to set email alerts
|

Surface Colonization and Activity of the 2,6-Dichlorobenzamide (BAM) Degrading Aminobacter sp. Strain MSH1 at Macro- and Micropollutant BAM Concentrations

Abstract: Aminobacter sp. MSH1 uses the groundwater micropollutant 2,6-dichlorobenzamide (BAM) as a C and N source and is a potential catalyst for biotreatment of BAM-contaminated groundwater in filtration units of drinking water treatment plants (DWTPs). The oligotrophic environment of DWTPs including trace pollutant concentrations, and the high flow rates impose challenges for micropollutant biodegradation in DWTPs. To understand how trace BAM concentrations affect MSH1 surface colonization and BAM degrading activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…Based on biovolume calculations of MSH1-GFP biofilms, specific BAM degradation rates at micropollutant concentrations were the same in both flow chamber experiments (with and without reduction of AOC) as those reported by Sekhar et al (10) and hence were 100-fold lower than those found for fresh cells in suspended batch conditions. The instability of the Dcba ϩ phenotype might be a cause of reduced activity, since it will result in cells that cannot gain energy from the available BAM.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Based on biovolume calculations of MSH1-GFP biofilms, specific BAM degradation rates at micropollutant concentrations were the same in both flow chamber experiments (with and without reduction of AOC) as those reported by Sekhar et al (10) and hence were 100-fold lower than those found for fresh cells in suspended batch conditions. The instability of the Dcba ϩ phenotype might be a cause of reduced activity, since it will result in cells that cannot gain energy from the available BAM.…”
Section: Discussionsupporting
confidence: 73%
“…Below feed concentrations of 100 g/liter BAM, the growth of MSH1 is due mainly to residual assimilable organic carbon (AOC) present in the minimal medium. Moreover, MSH1-specific BAM-degrading activity was reduced 100-fold compared to that of freshly grown cells due to C and/or N starvation (10). A similar reduction in specific BAM-degrading activity was found in a DWTP pilot-scale sand filter study that investigated bioaugmentation with Aminobacter sp.…”
supporting
confidence: 67%
See 3 more Smart Citations